Proceedings of the 2019 Conference of the North 2019
DOI: 10.18653/v1/n19-4021
|View full text |Cite
|
Sign up to set email alerts
|

Community lexical access for an endangered polysynthetic language: An electronic dictionary for St. Lawrence Island Yupik

Abstract: In this paper, we introduce a morphologicallyaware electronic dictionary for St. Lawrence Island Yupik, an endangered language of the Bering Strait region. Implemented using HTML, Javascript, and CSS, the dictionary is set in an uncluttered interface and permits users to search in Yupik or in English for Yupik root words and Yupik derivational suffixes. For each matching result, our electronic dictionary presents the user with the corresponding entry from the Badten et al. (2008) Yupik-English paper dictionary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…This has been possible using a morphologically aware dictionary. In the system, a strategy of multiple input methods has been intro-duced that caters to different writing systems (Hunt et al, 2019). The work here is tailor-made, and it maintains a strong link between the language and its community.…”
Section: Related Workmentioning
confidence: 99%
“…This has been possible using a morphologically aware dictionary. In the system, a strategy of multiple input methods has been intro-duced that caters to different writing systems (Hunt et al, 2019). The work here is tailor-made, and it maintains a strong link between the language and its community.…”
Section: Related Workmentioning
confidence: 99%
“…In this section, we present some of the recent work on online dictionaries, which is heavily guided by the needs of one individual language. Our infrastruc-¹Skolt word for stream A recent dictionary for St. Lawrence Island Yupik (Hunt et al, 2019) combines Foma-based morphological analyzers with an HTML based search interface. Unlike Akusanat, which does the morphological analysis and generation in the cloud, their solution runs the transducers on the client side with Foma's Javascript integration.…”
Section: Related Workmentioning
confidence: 99%
“…2 Designing for a Reusable API It is not uncommon that similar tools and methods are developed by different research groups in different parts of the world for language documentation purposes. To name a few, there are projects developing similar language documentation systems for African languages (Jones and Muftic, 2020), Indonesian languages (Nasution et al, 2018) and Yupik (Hunt et al, 2019), while at the same time, it has been shown that digital humanities projects that are seemingly different, still face the very same technical problems (Mäkelä et al, 2020). In arguably, any work conducted with endangered languages to document them and better serve the small community of speakers has a lot of value.…”
Section: Introductionmentioning
confidence: 99%